Budaya Pengamalan Nilai-Nilai Pancasila di Lingkungan Sekolah: Studi Etnografi di SMA Negeri 3 Rantau Utara - Afranisha Afranisha; Wanda Fahira; Muhammad Rafli Ashari; Rohana Rohana (Pancasila and Civics Education Journal, 2026)
Abstract: This study aims to examine the understanding and appreciation of Pancasila values among grade X-3 high school students in their daily lives at school. The focus on grade X-3 was chosen because students at this level are experiencing an identity transition from junior high school to a more critical mindset of early adolescence, making the process of internalizing values very crucial and vulnerable. The study used a qualitative approach with an ethnographic design through participatory observation, in-depth interviews, and behavioral documentation of grade X-3 students, PPKn teachers, and homeroom teachers. Data analysis was conducted inductively referring to the Miles and Huberman model. The results showed that most grade X-3 students were at the responding to valuing stage in Krathwohl's affective taxonomy, where compliance still relies heavily on external supervision. School culture, particularly morning routines, peer interactions, and teacher role models, proved to be determinants in the formation of civic character. The conclusion of the study emphasized the need for a character strengthening program that is contextual, participatory, and responsive to the characteristics of the psychosocial development of grade X-3 adolescents.Keywords: School Culture; Ethnography of Education; Internalization of Values, PancasilaAbstrak: Penelitian ini bertujuan mengkaji pemahaman dan penghayatan nilai-nilai Pancasila pada peserta didik kelas X-3 SMA dalam kehidupan sehari-hari di lingkungan sekolah. Fokus pada kelas X-3 dipilih karena siswa pada jenjang ini tengah mengalami transisi identitas dari jenjang SMP menuju pola pikir remaja awal yang lebih kritis, sehingga proses internalisasi nilai menjadi sangat krusial sekaligus rentan. Penelitian menggunakan pendekatan kualitatif dengan desain etnografi melalui observasi partisipatif, wawancara mendalam, dan dokumentasi perilaku terhadap siswa kelas X-3, guru PPKn, serta wali kelas. Analisis data dilakukan secara induktif mengacu pada model Miles dan Huberman. Hasil penelitian menunjukkan bahwa sebagian besar siswa kelas X-3 berada pada tahap responding hingga valuing dalam taksonomi afektif Krathwohl, di mana kepatuhan masih sangat bergantung pada pengawasan eksternal. Budaya sekolah, khususnya pembiasaan pagi, interaksi antarteman sebaya, dan keteladanan guru, terbukti menjadi faktor determinan dalam pembentukan karakter kewarganegaraan. Simpulan penelitian menegaskan perlunya program penguatan karakter yang kontekstual, partisipatif, dan responsif terhadap karakteristik perkembangan psikososial remaja kelas X-3.Kata Kunci: Budaya Sekolah; Etnografi Pendidikan; Internalisasi Nilai, Pancasila